Effects of a 4-Week Plyometric Box Jump Training Program on 50m Breaststroke Performance in Competitive Swimmers - Indri Patricia A Sinaga; Yagmur Tosun; Samsuddin Siregar; Jet C. Longakit (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. The objective of this study is to examine the influence of a four-week plyometric box jump training regimen on the performance of competitive swimmers in the 50m breaststroke event, with a particular focus on evaluating alterations in sprint duration, stroke mechanics, and power output. Materials and methods. Ten competitive swimmers (ages 18-25) with minimum 3 years experience were randomly assigned to experimental (n=5) and control (n=5) groups. The experimental group completed a 4-week plyometric box jump training program (3 sessions/week) alongside regular swim training, while the control group maintained only regular swim training. Pre- and post-intervention measurements included 50m breaststroke time trials, stroke rate, stroke length, vertical jump height, and post-exercise blood lactate levels. Results. The experimental group showed significant improvements in 50m breaststroke performance with an average time reduction of 4.967 seconds (p < 0.05). They demonstrated increased stroke rate without compromising stroke length, suggesting enhanced power efficiency. The experimental group (-5.758s) showed greater improvement compared to the control group (-3.980s). Statistical analysis confirmed significance with calculated t-value (2.625717) exceeding critical t-value (2.26216). Conclusions. A 4-week plyometric box jump training program can significantly enhance 50m breaststroke performance in competitive swimmers through improved power generation and stroke mechanics. The program effectively develops explosive strength and neuromuscular coordination specific to breaststroke requirements without compromising technique.